2012
DOI: 10.5171/2012.693619
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents to Consumer Ethnocentrism: A Fuzzy Logic-Based Analysis Study

Abstract: This study empirically examines a segment of consumers within the Jordanian society who express high ethnocentric tendencies towards domestic products using fuzzy logic technique. MATLAB® ANFIS has been employed to model the relationships between three inputs (conservatism, dogmatism and world-mindedness) and one output (consumer ethnocentrism). The results of this research conclude that Sugeno type fuzzy model has the ability to predict precisely consumers ethnocentric tendencies levels based on their socio-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Hence, consumers with a higher level of world-mindedness would probably express higher consumer xenocentrism and lower consumer ethnocentrism. The negative relationship between world-mindedness and consumer ethnocentrism was empirically verified in Jordanian consumers [45] and other research found a positive relationship between worldmindedness and xenocentrism [46]. Another study [47] posited that world-mindedness was positively related to foreign consumer culture positioning (FCCP) and global consumer culture positioning (GCCP) while negatively related to local consumer culture positioning (LCCP).…”
Section: ) Consumer Sentimentsmentioning
confidence: 88%
“…Hence, consumers with a higher level of world-mindedness would probably express higher consumer xenocentrism and lower consumer ethnocentrism. The negative relationship between world-mindedness and consumer ethnocentrism was empirically verified in Jordanian consumers [45] and other research found a positive relationship between worldmindedness and xenocentrism [46]. Another study [47] posited that world-mindedness was positively related to foreign consumer culture positioning (FCCP) and global consumer culture positioning (GCCP) while negatively related to local consumer culture positioning (LCCP).…”
Section: ) Consumer Sentimentsmentioning
confidence: 88%
“…The causal relationship between world-mindedness and consumer ethnocentrism has been studied by many researchers. Many researchers revealed that world-mindedness is the antecedent of consumer ethnocentrism (Al Ganideh et al, 2012;Shankarmahesh, 2006;Siemieniako et al, 2011). The review study of Shankarmahesh (2006) concluded that world-mindedness has a negative effect on consumer ethnocentrism.…”
Section: World-mindednessmentioning
confidence: 99%
“…The review study of Shankarmahesh (2006) concluded that world-mindedness has a negative effect on consumer ethnocentrism. Furthermore, some empirical studies found that consumer ethnocentrism is influenced by world-mindedness (Al Ganideh et al, 2012;W. N. Lee et al, 2003).…”
Section: World-mindednessmentioning
confidence: 99%
See 2 more Smart Citations